The study of inter-relationship among secondary hyperparathyroidism and vitamin D3 deficiency in obese diabetics and obese non-diabetic patients - Imad Jassim Mohammad; Soheila Kashanian; Ronak Rafipour; Husam Aljwaid; Sadegh Hashemi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Adiposity is connected to vitamin D3 (Vit. D3) deficiency and hyperthyroidism. Type 2 diabetes (T2D) is associated with Vit. D3 deficiency. Our study aims to assess the inter-relationship among Vit. D3 deficiency and secondary hyperparathyroidism in obese diabetic and non-diabetic patients. Methods: Our study included 90 patients (45 obese type 2 diabetics and 45 obese non-diabetics as control). Serum Vit. D3, serum parathyroid hormone (PTH), calcium, leptin, fasting blood sugar (FBS), serum insulin, insulin resistance (HOMA-IR), hemoglobin A1C (HbA1c), and body mass index (BMI) were measured. Results: The levels of Vit. D3 deficiency were 100% in obese diabetics and non-diabetic patients 17.43 ±3.94 and 13.95 ±4.60, respectively. The association was inversely related to BMI in the obese diabetic patients (r=-0.36, P=0.01) and non-diabetic (r=-0.18, P=0.23). While the correlation was positive as well as significant (r=0.49, P<0.001) between PTH levels with BMI in obese diabetic subjects with a mean of 44.10 ±14.01, 13.3% have elevated PTH levels, the correlation was positive and no significant with BMI (r=0.06, P<0.6) through obese non-diabetics the mean was 57.19 ±17.71, and 35.5% of them had a high level of PTH. Our results showed a very weak and no significant negative correlation between Vit. D3 and PTH in each of the obese diabetics and obese non-diabetic groups (r=-0.12, P=0.4) and (r=-0.24, P=0.1), respectively. Serum concentration of leptin has significantly associated with body mass index (r=0.94, P<0.001) in obese diabetic through (r=0.3, P=0.04) in control. The most surprising finding is the very strong association between HOMA-IR with BMI in non-diabetics (r=0.87, P <0.001). Conclusion: Adiposity is a risk factor for T2D related to Vit. D3 deficiency and high level of PTH. The correlation between Vit. D3 deficiency and PTH is inverse and insignificant